Impact of trade liberalization on government finances in Jamaica (ECLAC Port of SpainTT, 1999)
Examines the effects of trade liberalization and the fluctuations of commodity prices and income from services on public finance in Jamaica.
Keywords: TRADE LIBERALIZATION